2009
DOI: 10.1007/s10728-009-0115-2
|View full text |Cite
|
Sign up to set email alerts
|

Successful Priority Setting in Low and Middle Income Countries: A Framework for Evaluation

Abstract: Priority setting remains a big challenge for health managers and planners, yet there is paucity of literature on evaluating priority setting. The purpose of this paper is to present a framework for evaluating priority setting in low and middle income countries. We conducted a qualitative study involving a review of literature and Delphi interviews with respondents knowledgeable of priority setting in low and middle income countries. Respondents were asked to identify the measures of successful priority setting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
81
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(83 citation statements)
references
References 18 publications
2
81
0
Order By: Relevance
“…According to the World Health Organization, a health research prioritization process is defined as a scheme to build consensus on a set of research issues that require urgent attention [20]. A priority is defined as an element or condition judged to be more important than another, which involves an exercise in “judgment” and the use of “values” that sustain the quality of a priority [21].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the World Health Organization, a health research prioritization process is defined as a scheme to build consensus on a set of research issues that require urgent attention [20]. A priority is defined as an element or condition judged to be more important than another, which involves an exercise in “judgment” and the use of “values” that sustain the quality of a priority [21].…”
Section: Introductionmentioning
confidence: 99%
“…Simultaneously, there is a local context and a series of criteria, such as benefits, evidence, cost-efficiency, equity, and severity, which compete in order to establish this judgment. Finally, stakeholders, who act individually in representation of pluralist society, make decisions by consensus, making an ethical framework necessary to sustain the legitimacy of the prioritization process [2,20]. This group of stakeholders includes individuals from the governmental sector, non-governmental organizations, the private sector, academia, health service providers, and healthcare recipients.…”
Section: Introductionmentioning
confidence: 99%
“…These authors suggested that their research was an "initial attempt to evaluate priority setting decisions in a specific context" and that "future research is required to determine the best combination of components" -building on this work, we have adapted many of their dimensions into our model of high performance. Kapiriri and Martin (2009) Canada could serve at a minimum as a starting point for discussion in other settings as well.…”
Section: Discussionmentioning
confidence: 99%
“…Fifth, the framework of A4R was purposively selected to evaluate the prioritization process of the project. There are, however, other evaluation tools that can be applied for assessing the resource allocation process such as a framework of internal and external parameters for evaluating successful priority setting in low-and middle-income countries [33] and a checklist for assessing nine common themes of good practice for health research priority setting [34]. It is noteworthy that decision making in itself is a dynamic process, and some interventions' performance on some criteria used for example, severity of disease, effectiveness of interventions, or economic impact of household expenditure, is likely to change over time.…”
Section: Discussionmentioning
confidence: 99%